Identifying Learning Styles of Grade Six Students - Fitrianasari, Rosalina; Nurhayati, Nurhayati (Program Studi Ilmu Perpustakaan, Fakultas Ilmu Budaya, Universitas Diponegoro, 2024)
This study was conducted to find out the students’ learning styles and how to overcome based on their learning styles in the students of grade six at Primary Global Islamic School Jakarta. The method that is used in this study is descriptive qualitative method. The data were obtained through questionnaire. The questionnaire is developed using true-false items. The result shows there are 3 learning styles that are found, those are auditory, visual, and kinesthetic learning styles such as (1) increasing field trips, (2) direct demonstrating and performing, (3) the process of learning does not have to sit like formal, (4) making various examples, (5) increasing simulation or role play, (6) allowing students to move or to stand, (7) do not force students to learn for a long time, (8) encourage the students to use bright marker to highlight important thin in their reading. Kinesthetic learning style is the dominant. It shows that most of the students can understand the material with kinesthetic style. To overcome the students’ learning style, the teachers’ role is very important. By knowing students’ learning styles, it will help the teachers to set the teaching styles, so the goals of teaching will be achieved and the students can acquire their goals.